Effects of Native Fucosylated Glycosaminoglycan, Its Depolymerized Derivatives on Intrinsic Factor Xase, Coagulation, Thrombosis, and Hemorrhagic Risk - Zhou, Lutan; Gao, Na; Sun, Huifang; Xiao, Chuang; Yang, Lian; Lin, Lisha; Yin, Ronghua; Li, Zi; Zhang, Hongbin; Ji, Xu; Zhao, Jinhua (Thrombosis and Haemostasis, 2020)
A native fucosylated glycosaminoglycan from sea cucumber Holothuria fuscopunctata (nHG), mainly branched with Fuc3S4S, exhibited potent anticoagulant activity by intrinsic tenase iXase (FIXa-FVIIIa complex) and antithrombin-dependent factor IIa (FIIa) inhibition, but also had the effects of FXII activation and platelet aggregation. For screening a selective iXase inhibitor, depolymerized nHG (dHG-1 ∼ –6) and a pure octasaccharide (oHG-8) were prepared. Like nHG, dHG-1 ∼ –6 and oHG-8 could potently inhibit iXase, and competitive binding assay indicated that dHG-5 and oHG-8 could bind to FIXa. Nevertheless, dHG-5 and oHG-8 had no effects on FXII and platelet activation. nHG, dHG-5, and oHG-8 could significantly prolong the activated partial thromboplastin time of human, rat, and rabbit plasma. In the rat deep venous thrombosis model, dHG-5 and oHG-8 showed potent antithrombotic effects in a dose-dependent manner, while the thrombus inhibition rate of nHG at high dose was markedly reduced. Additionally, dHG-5 and oHG-8 did not increase bleeding at the doses up to 10-fold of the effectively antithrombotic doses compared with nHG and low molecular weight heparin in the mice tail-cut model. Considering that dHG-5 possesses strong anti-iXase and antithrombotic activities, and its preparation process is simpler and its yield is higher compared with oHG-8, it might be a promising antithrombotic candidate.
Keywords: dHG-5; iXase; anticoagulant; antithrombotic; hemorrhagic risk